Effectiveness of Micro-Credit for Poverty Alleviation Under Agricultural Intensification Projects in Bangladesh - Mahmud, Kazi Tanvir (2006)
The rural poor generally have low income to sustain their livelihood. They do not have the capacity to start any income generating activities due to lack of financial capital. They also have very limited access to the formal financial institutions because of the inability to fulfill the collateral requirements. Thus, in order to widen the rural poor’s access to finance, microcredit programs have been launched which require no collateral to obtain loans. The major goal of the microcredit program is to provide financial capital to the rural poor in order to engage them in income generating activities for alleviating their poverty. The main objective of this study is to assess the effectiveness of microcredit program in alleviating poverty among rural borrowers in Bangladesh.